Challenges and Strategies of the Merdeka Belajar–Kampus Merdeka Policy at State Islamic Higher Education Institutions in Kalimantan - Sitti Rahmasari; Wiwik Agustinaningsih (Politeknik Siber Cerdika Internasional, 2026)
Background: The Merdeka Belajar–Kampus Merdeka (MBKM) policy is not easy to implement at universities, including State Islamic Higher Education Institutions. Therefore, this study aims to examine the challenges and strategies for implementing the MBKM policy at State Islamic Higher Education Institutions in Kalimantan. Objective: This study aims to identify and analyze the challenges encountered in implementing the MBKM policy at PTKINs in Kalimantan. Methods: Qualitative and quantitative techniques were used to explore the perspectives of study subjects regarding the challenges and strategies of the MBKM policy. Results: The challenges for implementing the MBKM policy include the absence of a guidebook issued by the State Islamic Higher Education Institutions as a foundation for implementation, the lack of adequate support, insufficient campus facilities and infrastructure, and the implementation of regulations requiring a considerably large budget. The implementation of the MBKM policy requires acquiring a guidebook issued by the State Islamic Higher Education Institutions based on the MBKM guidebook issued by the Ministry of Religion as a foundation for implementation, and formulating a curriculum in accordance with the requirements of the MBKM policy. Conclusion: MBKM implementation at PTKINs in Kalimantan is impeded by institutional, resource, and communication barriers that are distinct from those faced by general state universities. The study contributes an empirically grounded challenge-strategy framework specific to Islamic higher education governance in Indonesia.